A STUDY ON THE STUDENTS’ READING COMPREHENSION AT THE FIRST SEMESTER OF MANAGEMENT PROGRAM AT ISLAMIC UNIVERSITY OF INDRAGIRI TEMBILAHAN - Maizarah, Maizarah (Universitas Wiralodra, 2018)
The problem in this study was the students? reading comprehension on the first semester of Management Program at Islamic University of Indragiri Tembilahan. This research only used one variable was reading comprehension. The research method used in this study was a descriptive research. The purpose of this study was to know the students? reading comprehension on the first semester of Management program at Islamic University of Indragiri Tembilahan. The total of the population used in this study were 163 students, the technique was used to take the sample is random sampling, the sample of this study was 25% from the population were 41 students. In collecting the data, the researcher used a reading test. After the data has been collected, the result of test shows that the students? reading comprehension was categorized as Average to Good because 59,39 in range 51-75, it is mean that the students should be improve their reading comprehension to be better than it.